Immunomodulators in chronic rhinosinusitis - Philippe Lavigne (KeAi Communications Co., Ltd., 2018)
Objective: To provide new insight into how chronic rhinosinusitis (CRS) is conceptualized and treated with a focus on immunomodulator therapy. Data sources: Pubmed, Medline, and Embase. Methods: A current review of the evidence is provided for immunomodulators investigated for treatment of CRS with nasal polyps (CRSwNP). Results: Biologic therapies targeting IgE, IL-4, IL-5, and IL-13 for the treatment of CRSwNP have shown promise and are currently in phase 3 trials. Anti-immunoglobin E (IgE) therapy with omalizumab was assessed in 6 studies, anti-interleukin (IL)-5 therapy in 3 studies (2 mepolizumab, 1 reslizumab) and anti IL-4/IL-13 (dupilumab) therapy in one study. Studied outcomes varied, but the majority of trials identified clinical benefit of therapy over placebo. Other potential targets include thymic stromal lymphopoetin (TSLP), IL-25, IL-33, and sialic acid-binding immunoglobulin-type lectin (Siglec)-8. Small molecule drugs that target the dysregulation of the immune system in CRS are also being investigated for their immunomodulatory effects on inflammation. Conclusion: Immunomodulator therapies for CRS currently in development will likely provide another therapeutic option for patients who have severe disease unresponsive to corticosteroids and surgery. Targeted monoclonal antibody therapies have shown encouraging results and phase 3 trials are underway. IL-4/IL-13 inhibition has shown the most promise to date. Further larger, well-designed trials are needed to improve understanding of these molecules and to offer endotype-driven therapies in the management of CRS. None of these therapeutics have shown long-term immunomodulation when discontinued and therefore further investigation into the pathomechanism of disease continues to be needed. Keywords: Biologic, Immunotherapy, Chronic rhinosinusitis, Nasal polyps, Immunomodulator